Handbook of Positive Psychology, Religion, and Spirituality - Davis, Edward B.; Worthington Jr., Everett L.; Schnitker, Sarah A. (Springer Nature, 2023)
This handbook aims to bridge the gap between the fields of positive psychology and the psychology of religion and spirituality. It is the authoritative guide to the intersections among religion, spirituality, and positive psychology and includes the following sections: (1) historical and theoretical considerations, (2) methodological considerations, (3) cultural considerations, (4) developmental considerations, (5) empirical research on happiness and well-being in relation to religion and spirituality, (6) empirical research on character strengths and virtues in relation to religion and spirituality, (7) clinical and applied considerations, and (8) field unification and advancement. Leading positive psychologists and psychologists of religion/spirituality have coauthored the chapters, drawing on expertise from their respective fields. The handbook is useful for social and clinical scientists, practitioners in helping professions, practitioners in religious and spiritual fields, and students of psychology and religion/spirituality. This is an open access book.